INTERNET ADVERTISING AND CONSUMPTIVE LIFESTYLE OF THE STUDENTS - Rully Khairul Anwar; Elnovani Lusiana; Mohammad Taufiq Rahman (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2019)
This paper discusses about how mass media as part of society has been widely used in addition being a media of information and entertainment, as well as a media of persuasion. In this case the researcher looked at the exposure of internet advertising that was part of the effort to promote goods and services from producers to the public as consumers. Researchers were intrigued to find out more about whether advertisements on internet mass media that contain more commercial advertisements and become part of economic activities can affect the behavior of students as teenagers that can lead to consumptive nature that is used to be a lifestyle. The student's consumptive lifestyle as a result of being hit by advertisements on the internet mass media is seen from the number of goods ownership such as female students who have a number of beauty equipment with different brands and gadget more than one. And men are more visible on gadgets alone, they are more likely to have more than one gadget, even though one of them can still be used.